Selection and Evaluation of a Thornless and HLB-Tolerant Bud-Sport of Pummelo Citrus With an Emphasis on Molecular Mechanisms - Wu, Bo; Li, Na; Deng, Zhanao; Luo, Feng; Duan, Yongping (Frontiers in Plant Science, 2021)
The selection of elite bud-sports is an important breeding approach in horticulture. We discovered and evaluated a thornless pummelo bud-sport (TL) that grew more vigorously and was more tolerant to Huanglongbing (HLB) than the thorny seedling wild type (W). To reveal the underlying molecular mechanisms, we carried out whole-genome sequencing of W, and transcriptome comparisons of W, TL, and partially recovered thorny ‘mutants’ (T). The results showed W, TL, and T varied in gene expression, allelic expression, and alternative splicing. Most genes/pathways with significantly altered expression in TL compared to W remained similarly altered in T. Pathway and gene ontology enrichment analysis revealed that the expression of multiple pathways, including photosynthesis and cell wall biosynthesis, was altered among the three genotypes. Remarkably, two polar auxin transporter genes, PIN7 and LAX3, were expressed at a significantly lower level in TL than in both W and T, implying alternation of polar auxin transport in TL may be responsible for the vigorous growth and thornless phenotype. Furthermore, 131 and 68 plant defense-related genes were significantly upregulated and downregulated, respectively, in TL and T compared with W. These genes may be involved in enhanced salicylic acid (SA) dependent defense and repression of defense inducing callose deposition and programmed cell death. Overall, these results indicated that the phenotype changes of the TL bud-sport were associated with tremendous transcriptome alterations, providing new clues and targets for breeding and gene editing for citrus improvement.